Isolation of Pasteurella multocida from broiler chickens - Poernomo, Sri; Sarosa, A (Indonesian Animal Sciences Society, 1996)
Pasteurella multocida, the etiological agent of fowl cholera, was isolated from five, 32 days oldbroilerchickens in the late of 1992. The chickens were from a farm located in Bogor area, raised in cages and each flock consisted of 1,550 broilers . Therewere 230 birds, aging from 28-31 days old, died with clinical signs of lameness and difficulty in breathing. Serological test of the isolate revealed serotype Aof Carter classification . To prove Â its virulences, the isolate was then inoculated into 3 mice subcutaneously. The mice died less then 24 hours postinoculation and P. multocida can be reisolated . The sensitivity test to antibiotics and sulfa preparations showed that the isolate was sensitive to ampicillin, doxycyclin, erythromycin, gentamycin, sulfamethoxazol-trimethoprim and baytril, but resistance to tetracyclin, kanamycin and oxytetracyclin. This is the first report of P. multocida isolation in broiler chickens in Indonesia, and it is intended to add information on bacterial diseases in poultry in Indonesia. Â Keywords : Pasteurella multocida, isolation, broiler chickens, antibiotics